2020
DOI: 10.3390/ijerph17145006
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Perspectives of a School-Based Intervention to Promote Active School Transportation

Abstract: There is a global need for sustainable interventions that increase physical activity among children, and active school transportation (AST) can promote physical activity among schoolchildren. Therefore, an intervention based on gamification, empowerment, and social cognitive theory was initiated in 2016 to promote AST. The aim of this study was to follow up on participants’ experiences one and two years after the AST intervention was initiated. Data were collected through focus groups and individual interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…From observing the participants during the event, in addition to participants being competitive, they seemed to enjoy the collaborative aspect of the game, which is also supported by the questionnaire. This signifies the importance of collaboration as a motivation for gamification [9,24], which is also important in behavioral change [36]. In Table 9, we used the eight core Octalysis framework to highlight the required improvement in the future version of the game.…”
Section: Discussionmentioning
confidence: 99%
“…From observing the participants during the event, in addition to participants being competitive, they seemed to enjoy the collaborative aspect of the game, which is also supported by the questionnaire. This signifies the importance of collaboration as a motivation for gamification [9,24], which is also important in behavioral change [36]. In Table 9, we used the eight core Octalysis framework to highlight the required improvement in the future version of the game.…”
Section: Discussionmentioning
confidence: 99%
“…These results emphasize the importance of creating supportive environments for health-promoting PA behaviors such as AST [ 46 ]. Here, interventions might also play an important role, supporting both parental strategies (i.e., trusting the child and learning to navigate in traffic) [ 33 ] as well as developing children’s skills [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the research of the strategies implemented to encourage the use of this type of mobile applications by young people, we found that it is necessary to innovate regularly with different ideas, requiring an interactive design, ease of use, frequent updating of information, use of questionnaires as interaction with young people, use of gamification and promoting benefits from using the application [26][27][28][29][30].…”
Section: Related Workmentioning
confidence: 99%